Dose-response relationship of specific training to reduce chronic neck pain and disability - Nikander, Riku; Mälkiä, Esko; Parkkari, Jari; Heinonen, Ari; Starck, Heli; Ylinen, Jari (Medicine and science in sports and exercise, 2006)
To examine the dose-response relationship of specific strength- and endurance-training regimes for the cervical muscles, which have been shown to be effective among women with chronic neck pain and disability. A total of 180 female office workers, aged 25 to 53 yr, with chronic neck pain and disability were randomized into a strength-training, an endurance-training, and a control group. The training groups participated in a 12-d rehabilitation period, in which instructions for the exercises were given by an experienced physical therapist. Both training groups continued with exercises at home for 12 months. Physical activity was measured with a training diary and a 1-month all-time recall questionnaire. All activities were registered and converted into metabolic equivalents (METs). Specific neck, shoulder, and upper-extremity training for more than 8.75 MET.h.wk was an effective training dose for decreasing neck pain. One MET-hour of training per week accounted for an 0.8-mm decrease of neck pain on a visual analog scale (VAS) and a 0.5-mm decrease on a disability index. Both strength and endurance training decreased perceived neck pain and disability. Declines in neck pain and disability correlated positively with the amount of specific training. This study revealed that the described specific exercise protocols were associated with decreases in chronic neck pain and disability. The effective dose of training was feasible and safe to perform among female office workers.